Biological wastewater treatment - Grady, C. P. Leslie, 1938- (Environmental science & pollution ;, 2011)
Introduction and BackgroundClassification of Biochemical OperationsThe Role of Biochemical OperationsCriteria for ClassificationCommon "Named" Biochemical OperationsKey PointsStudy QuestionsReferencesFundamentals of Biochemical OperationsOverview of Biochemical OperationsMajor Types of Microorganisms and Their RolesMicrobial Ecosystems in Biochemical OperationsImportant Processes in Biochemical OperationsKey PointsStudy QuestionsReferencesStoichiometry and Kinetics of Aerobic/Anoxic Biochemical OperationsStoichiometry and Generalized Reaction RateBiomass Growth and Substrate UtilizationSoluble.